2018
DOI: 10.1002/adsc.201800488
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β‐Trifluoromethylated Alkyl Azides via a Manganese‐Catalyzed Trifluoromethylazidation of Alkenes with CF3SO2Na and TMSN3

Abstract: A convenient and efficient manganese‐catalyzed trifluoromethylazidation of alkenes has been developed by utilizing inexpensive and readily available CF3SO2Na under mild conditions. The various β‐trifluoromethylated alkyl azides were directly obtained from corresponding allyl, vinyl, chain terminal and internal alkenes, and easily further transformed into other CF3‐containing compounds.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 126 publications
2
13
0
Order By: Relevance
“…Based on the above results and previous literature, a plausible mechanistic interpretation is depicted in Scheme 3[22,[24][25][26][27][28][29][30][31]. Initially, CF 3 SO 2…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Based on the above results and previous literature, a plausible mechanistic interpretation is depicted in Scheme 3[22,[24][25][26][27][28][29][30][31]. Initially, CF 3 SO 2…”
supporting
confidence: 64%
“…When a radical inhibitor, including TEMPO (2,2,6,6-tetramethyl-1-piperidinyloxy) and BHT (butylated hydroxytoluene), was added, the reaction was dramatically suppressed, implying that a radical reaction pathway might be involved in the catalytic cycle. Based on the above results and previous literature, a plausible mechanistic interpretation is depicted in Scheme 3 [22,[24][25][26][27][28][29][30][31]. Initially, CF3SO2 -reacts with t BuOOH to form •CF3 (A).…”
Section: Resultsmentioning
confidence: 58%
“…Other oxidants, such as PhI(OAc) 2 , K 2 S 2 O 8 and TBHP did not enhance the product yield ( Table 1, entries [2][3][4][5]. Subsequently, some organic solvents including dichloromethane (DCM), dichloroethane (DCE), toluene, tetrahydrofuran (THF), dimethyl formamide (DMF) and dimethylsulfoxide (DMSO) were explored (Table 1, entries 1,[6][7][8][9][10][11], and found that dichloromethane (DCM) was the optimal solvent for this transformation. After obtained the optimal oxidant and solvent, we tried to reduce the amounts of substrates 2 a and 3.…”
Section: Resultsmentioning
confidence: 99%
“…[5] In a subsequent work, they disclosed a cascade reaction of alkenes with TMSN 3 and acrylonitrile. [6] In 2018, Zhang group developed a manganese-catalyzed trifluoromethylazidation of unactivated alkenes by cascade reaction, [7] and Reiser et al reported a highly versatile visible-light photocatalytic strategy for the step-economical synthesis of α-azidoketones. [8] However, the development of cascade reaction to quickly build organoazides remains a standing challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] Tandem reaction processes incorporating multistep reactions into a single one pot procedure provide elegant routes to complex carbon or hetero frameworks from relatively simple precursors, thus highlighting the fundamental demands of an "ideal synthesis". [3] Over the past few decades, significant research efforts have been devoted to developing organic synthetic methodology focused on environmentally benign, atom-economical, operational simplicity pathways, taking into account the purpose of "green environmental protection and sustainability". Propargyl alcohols and their derivatives, bearing alkynyl and hydroxyl (ester) functional groups, have become increasingly important starting materials and have been extensively used as building blocks for the synthesis of functional materials, pharmaceuticals, and bioactive compounds.…”
mentioning
confidence: 99%